2011
DOI: 10.1007/s12275-011-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sgr3394 produced only by the A-factor-producin Streptomyces griseus IFO 13350, not by the A-factor deficient mutant

Abstract: Protein D (9.7 kDa) is an extracellular protein detected in the culture broth of A-factor-producing Streptomyces griseus IFO 13350, but not of the A-factor-deficient mutant strain S. griseus HH1. Comparison of the N-terminal amino acid sequence with the genomic sequencing data of S. griseus IFO 13350 identified protein D as Sgr3394, which encodes a putative secretory protein with unknown function. The premature Sgr3394 consisted of 128 amino acids (13.5 kDa), showed 87.5% identity with SACT1DRAFT-0503, from St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In conclusion, we suggest that moenomycin biosynthesis, not regulated at the pathway-specific level [13, 18], is still a subject for global regulation from LSM-dependent pathways. S. ghanaensis genome analysis witnesses the presence of gene sets for synthesis and reception of two butenolide-like classes of LSMs, that of γ-butyrolactone and avenolide families.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we suggest that moenomycin biosynthesis, not regulated at the pathway-specific level [13, 18], is still a subject for global regulation from LSM-dependent pathways. S. ghanaensis genome analysis witnesses the presence of gene sets for synthesis and reception of two butenolide-like classes of LSMs, that of γ-butyrolactone and avenolide families.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological differentiation and secondary metabolism of the Streptomyces are simultaneously controlled by environmental nutrients, such as carbon, nitrogen, phosphorus, and trace elements. A pleiotropic autoregulatory factor (A-factor, 2-isocapryloyl-3R-hydroxymethyl-Ȗ-butyrolactone) triggers both morphological and physiological differentiation of Streptomyces (Horinouchi et al, 1984;Hong et al, 1993;Horinouchi and Beppu, 1994;Chater and Horinouchi, 2003;Kato et al, 2005;Horinouchi, 2007;Chi et al, 2011). Rigali et al (2008) recently showed that the pleiotropic transcriptional repressor DasR triggers antibiotic production through the response of Streptomyces to environmental nutrient stress.…”
mentioning
confidence: 99%